Psocids from Malta (Insecta: Psocodea: ‘Psocoptera’), with new synonymy for Peripsocus stagnivagus based on the discovery of its first Palaearctic male - Lienhard, Charles; Mifsud, David (Zootaxa, 2015)
About 2,000 specimens of Psocoptera were collected in Malta recently. Examination of this material revealed 21 new records for the Maltese archipelago, augmenting the known psocid fauna of these islands from 6 to 27 species. One of the most abundant species is Peripsocus stagnivagus Chapman, 1930 (= P. bivari Baz, 1988 = P. leleupi Badonnel, 1976, new synonymies), formerly considered to be a predominantly Nearctic species. The discovery in Malta, of one male of this usually parthenogenetic species enabled comparison of this first Palaearctic male with the well-documented, rare Nearctic male. The lack of any morphological difference between these males, or between females from the Nearctic, the western Palaearctic and several Atlantic islands, supports the proposed synonymies.